FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN LAYANAN KESEHATAN DI PEMUKIMAN KUMUH KELURAHAN KARUWISI KECAMATAN PANAKUKKANG MAKASSAR - Muh Rifo Rianto; Syaifullah Cangara; Rahmat Muhammad (Lembaga Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Muhammadiyah Makassar, 2016)
Public health services in urban slums Karuwisi District of Makassar member a question into the background in this study The aim of the research is to describe the utilization of health services and factors related to the utilization of health services in slum residential area. The research method is qualitative approach with a case study. The research instrument is an in-depth interview and document study in data collection. Informers are communities residing in the area of slum residence. The results of the research indicated that the community’s responses on the symptoms or disease being suffered by them are varied, such as non-action, self-treatment, traditional remedy, modern health/private medication. Health service for the poor community enhances the efforts of the utilization of government health services, so that the community knows more about health services as a service needed urgently by poor community.